Performance of reinforced concrete and timber structure at Kuala Muda Kedah during the tsunami - Fateh, Amir; Hejazi, Farzad; Tarmizi, Megat Ahmad; Shoaei, Mohammad Dalili; Ghadiri, Seyed Mohammadreza (Academic Research Online Publisher, 2014)
An earthquake at the Richter scale of 9.3 occurred near northwest coast of Aceh Indonesia underneath Indian Ocean in 2004. This earthquake triggered series of large tsunamis that killed around 250,000 people including 68 deaths in Malaysia. The most affected areas in Malaysia territory were the northern coastal region especially at Kuala Muda, Kedah. The major focus of this study is investigation of the effect of tsunami on performance of buildings subjected to alteration of shear forces and moments. Behavior of engineered (reinforced concrete structure) and non-engineered (timber structure) buildings subjected to tsunami-induced forces comprising hydrodynamic and debris impact is discussed both types of structures existed in the devastated area. Site investigation showed non-engineered structures especially low-rise timber ones suffer a greater degree of structural and non-structural damages. According to the fact that from all key parameters related to run-up of tsunami, only the parameters related to trees which can block the Tsunami waves, may be controlled. So, the best way to reduce the run up is planting trees according to the suitable methods especially in area that directly faces the sea.